WITHDRAWN: Riluzole alleviates early neutrophil infiltration, brain oedema and lipid peroxidation in the traumatic brain tissue but does not induce neurotoxicity in non-traumatic brain tissue in rats - (:unkn) unknown (My University, 2014)
This article has been withdrawn at the request of the editor since, in breach of ethical guidelines and journal policies, the manuscript was submitted without the full knowledge and consent of all authors listed. The Publisher apologizes for any inconvenience this may cause. The full Elsevier Policy on Article Withdrawal can be found at http://www.elsevier.com/locate/withdrawalpolicy.